Histone Modifications, Internucleosome Dynamics, and DNA Stresses: How They Cooperate to “Functionalize” Nucleosomes - Krajewski, Wladyslaw A. (Frontiers in Genetics, 2022)
Tight packaging of DNA in chromatin severely constrains DNA accessibility and dynamics. In contrast, nucleosomes in active chromatin state are highly flexible, can exchange their histones, and are virtually “transparent” to RNA polymerases, which transcribe through gene bodies at rates comparable to that of naked DNA. Defining mechanisms that revert nucleosome repression, in addition to their value for basic science, is of key importance for the diagnosis and treatment of genetic diseases. Chromatin activity is largely regulated by histone posttranslational modifications, ranging from small chemical groups up to the yet understudied “bulky” ubiquitylation and sumoylation. However, it is to be revealed how histone marks are “translated” to permissive or repressive changes in nucleosomes: it is a general opinion that histone modifications act primarily as “signals” for recruiting the regulatory proteins or as a “neutralizer” of electrostatic shielding of histone tails. Here, we would like to discuss recent evidence suggesting that histone ubiquitylation, in a DNA stress–dependent manner, can directly regulate the dynamics of the nucleosome and their primary structure and can promote nucleosome decomposition to hexasome particles or additionally stabilize nucleosomes against unwrapping. In addition, nucleosome repression/ derepression studies are usually performed with single mononucleosomes as a model. We would like to review and discuss recent findings showing that internucleosomal interactions could strongly modulate the dynamics and rearrangements of nucleosomes. Our hypothesis is that bulky histone modifications, nucleosome inherent dynamics, internucleosome interactions, and DNA torsions could act in cooperation to orchestrate the formation of different dynamic states of arrayed nucleosomes and thus promote chromatin functionality and diversify epigenetic programming methods.